EVALUASI PENERAPAN PSAK 71 MENGENAI INSTRUMEN KEUANGAN PADA PT. SARANA SULUT VENTURA MANADO - Ilat, Veronica; Sabijono, Harijanto; Rondonuwu, Sintje (GOING CONCERN : JURNAL RISET AKUNTANSI, 2020)
Allowance for impairment losses are reserves that must be formed by the Bank to face the risk of loss due to investment. The purpose of this study is to compare PSAK 55 and 71 about financial instruments and recognition, measurement, especially about impairment and uncollectible financial assets and to find out how the implications are for companies after the adoption of PSAK 71 about financial instruments at PT North Sulawesi Venture Facility. Data analysis method used is descriptive qualitative. The results of the study found differences in the formation of CKPN in PSAK 55 appearing if an event occurred which resulted in the recognition of defaults and using the LIM Loss Incurred Method but in PSAK 71 CKPN at the beginning of the recognized period, using the ECL Expected Credit Loss method. In conclusion, the application of PSAK 71 to PT The North Sulawesi Venture Facility will begin in 2020 with the finalization of the December 2020 report, but the concrete impact will be on the number of CKPNs that become larger.